Is Scale-Up of Community Mobilisation among Sex Workers Really Possible in Complex Urban Environments? The Case of Mumbai, India - Kongelf, Anine; Bandewar, Sunita V. S.; Bharat, Shalini; Collumbien, Martine (PloS one, 2015)
In the last decade, community mobilisation (CM) interventions targeting female sex workers (FSWs) have been scaled-up in India's national response to the HIV epidemic. This included the Bill and Melinda Gates Foundation's Avahan programme which adopted a business approach to plan and manage implementation at scale. With the focus of evaluation efforts on measuring effectiveness and health impacts there has been little analysis thus far of the interaction of the CM interventions with the sex work industry in complex urban environments. Between March and July 2012 semi-structured, in-depth interviews and focus group discussions were conducted with 63 HIV intervention implementers, to explore challenges of HIV prevention among FSWs in Mumbai. A thematic analysis identified contextual factors that impact CM implementation. Large-scale interventions are not only impacted by, but were shown to shape the dynamic social context. Registration practices and programme monitoring were experienced as stigmatising, reflected in shifting client preferences towards women not disclosing as 'sex workers'. This combined with urban redevelopment and gentrification of traditional red light areas, forcing dispersal and more 'hidden' ways of solicitation, further challenging outreach and collectivisation. Participants reported that brothel owners and 'pimps' continued to restrict access to sex workers and the heterogeneous 'community' of FSWs remains fragmented with high levels of mobility. Stakeholder engagement was poor and mobilising around HIV prevention not compelling. Interventions largely failed to respond to community needs as strong target-orientation skewed activities towards those most easily measured and reported. Large-scale interventions have been impacted by and contributed to an increasingly complex sex work environment in Mumbai, challenging outreach and mobilisation efforts. Sex workers remain a vulnerable and disempowered group needing continued support and more comprehensive services.